Aid and state transition in Ghana and South Korea - Jiyoung Kim (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
This paper examines the questions of why and how foreign assistance was utilized successfully in South Korea but less so in Ghana, with a focus on the role of aid in the process of state building and state transition in these two countries. Before the 1960s, South Korea and Ghana shared approximately similar levels of GDP per capita. However, while South Korea achieved rapid economic development and democracy in one generation, Ghana suffered from slow development and a general deterioration of the standard of living. In particular, the state in South Korea played a critical role in achieving economic development, while the Ghanaian state, although relatively successful in carrying out recent economic reforms, is still far from becoming a fully effective developmental state. Adopting a comparative historical research method, the study explains the divergent paths of these two countries with a special focus on the impact of foreign assistance on state transitions. It argues that contextual factors - including the effect of colonial legacy in each of these two regions in shaping modern states and the specific characteristics of foreign assistance intervention - provide useful insights in explaining the differential impact of aid on state building and state transition in Ghana and in South Korea.
Keywords: F50; F54; H11; O10; O57; 330; Ghana; South Korea; foreign aid; state transition; state building